Preparation and gas-sensing properties of pitch-based carbon fiber prepared using a melt-electrospinning method - Kim, Jinhoon; Lee, Sung Ho; Park, Soo-Jin; Lee, Young-Seak (SPRINGER, 2014)
Pitch-based carbon fibers (PCFs) were fabricated using a melt-electrospinning method and used as a gas sensor electrode for nitric oxide (NO). The PCFs were modified through different heat-treatment temperatures (1,000, 1,650, and 2,300 A degrees C) and activation conditions (2, 4, and 6 M KOH solutions) to investigate the effect of these processes on the structure and surface functionalities of the resultant fiber samples. Field emission scanning electron microscopy, elemental analyzer, Raman spectroscopy, and pore analysis techniques were then employed to characterize the prepared samples. As a result of these modifications, the porosity and electrical conductivity of the prepared PCFs increased, which resulted in enlarged gas adsorption sites and an improved electron transfer. The improved porosity of the PCFs was attributed to the chemical activation process, whereas the enhanced electrical conductivity was also attributed to higher heat-treatment temperature. The sensing ability of the PCFs for NO-gas was thus significantly improved based on the effects of the chemical activation and higher heat-treatment temperatures. The performance of these PCFs as an NO-gas sensor system suggests promising application of carbon fibers as a novel and highly efficient NO-gas sensing material.
Keywords: MONOXIDE SENSORS; RAMAN-SPECTRUM; THIN-FILMS; NANOTUBES; OXIDE; ACTIVATION; POROSITY; NO